Applied geography : principles and practice : an introduction to useful research in physical, environmental and human geography - Pacione, Michael (Routledge, 1999)
Applied Geography offers an invaluable introduction to useful research in physical, environmental and human geography and provides a new focus and reference point for investigating and understanding problem-orientated research.